Brevibacillus sp: a novel thermophilic source for the production of bile salt hydrolase - Sridevi, N.; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2009)
A thermophilic microorganism growing within the temperature range of 40-65 A degrees C (optimum at 55 A degrees C) was isolated from hot water springs near Konkan, Maharashtra, India. Based on 16S rDNA sequence analysis, it was concluded that the isolate belongs to the genus Brevibacillus. The present paper reports the isolation, identification, and standardization of fermentation conditions for the production of enzyme, bile salt hydrolase (EC 3.5.1.24) which is produced intracellularly at high temperatures. This is the first report regarding the production of bile salt hydrolase from a thermophilic source. Optimization of fermentation conditions resulted in a 2.9-fold enhancement in enzyme production.
Keywords: Bile salt hydrolase; Brevibacillus sp; Fermentation; Glycodeoxycholic acid; Hot springs; Thermophile

Characterization of the smallest dimeric bile salt hydrolase from a thermophile brevibacillus sp. - Sridevi, N.; Srivastava, Sameer; Khan, Bashir Mohammad; Prabhune, Asmita Ashutosh (Extremophiles, 2009)
A thermophilic microorganism producing bile salt hydrolase was isolated from hot water springs, Pali, Maharashtra, India. This microorganism was identified as Brevibacillus sp. by 16S rDNA sequencing. Bile salt hydrolase (BSH) was purified to homogeneity from this thermophilic source using Q-sepharose chromatography and its enzymatic properties were characterized. The subunit molecular mass of the purified enzyme was estimated to be 28 kDa by SDS-PAGE and, 28.2 kDa by MALDI-TOF analysis. The native molecular mass was estimated to be 56 kDa by gel filtration chromatography, indicating the protein to be a homodimer. The pH and temperature optimum for the enzyme catalysis were 9.0 and 60A degrees C, respectively. Even though BSH from Brevibacillus sp. hydrolyzed all of the six major human bile salts, the enzyme preferred glycine conjugated substrates with apparent K (M) and k (cat) values of 3.08 mu M and 6.32 x 10(2) s(-1), respectively, for glycodeoxycholic acid. The NH2-terminal sequence of the purified enzyme was determined and it did not show any homology with other bacterial bile salt hydrolases. To our knowledge, this is the first report describing the purification of BSH to homogeneity from a thermophilic source.
Keywords: Bile salt hydrolase; Brevibacillus sp.; Dimeric intracellular enzyme; Purification; Thermophile